Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien dan Loyalitas Pasien di IGD RST Tk III Wirasakti Kupang - Gousario, Yongky; Niha, Simon S.; Yasinto, Yulius (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to evaluate patient perceptions of aspects of health services at RST TK III Wirasakti Kupang, including reliability, guarantee, direct evidence, empathy, and responsiveness. This research is a quantitative research with a cross sectional study design. The research results show that staff response, physical appearance, empathy, and consistency in service have a positive and significant effect on patient satisfaction. However, warranties have a negative influence on patient satisfaction. Patient satisfaction was then identified as a mediator that influences patient loyalty. Staff response, physical appearance, and empathy have a positive and significant effect on patient loyalty through satisfaction. On the other hand, reliability and guarantee have a negative but insignificant effect on patient loyalty through satisfaction.